Islamic Economic Review of Waste Circular Economy Policy Analysis at the Metro City Environmental Service - Yuniar, Irma; Syamsiyah, Nur; Yunarti, Yuyun (Jurnal Iqtisaduna, 2025)
This research aims to analyze the implementation of circular economy policy in waste management in Metro City and examine its relationship with Islamic economic principles. A circular economy is a strategic approach to creating a sustainable waste management system through seven main principles: reduce, reuse, recycle, recover, redesign, extended producer responsibility (EPR), and collaborative participation. Using a qualitative approach through observation, interviews, and documentation, this study found that the principles of reduce, reuse, and recycle have been implemented effectively thanks to education and community participation. Meanwhile, the principles of recovery and EPR still face obstacles, especially related to technological limitations and the non-optimal role of producers. From an Islamic economic perspective, implementing the circular economy aligns with the values of maslahah, Amanah, and khalifah fil arch, emphasizing the importance of responsible and equitable resource management. Thus, the circular economy has ecological and economic impacts and reflects Islamic spiritual ethics in protecting the environment and empowering communities.